Satellite Telemetry Reveals Spatial Overlap Between Vessel High-Traffic Areas and Humpback Whales (Megaptera novaeangliae) Near the Mouth of the Chesapeake Bay - Aschettino, Jessica M.; Engelhaupt, Daniel T.; Engelhaupt, Amy G.; DiMatteo, Andrew; Pusser, Todd; Richlen, Michael F.; Bell, Joel T. (Frontiers in Marine Science, 2020)
During winter months, humpback whales (Megaptera novaeangliae) frequent the coastal waters of Virginia near the mouth of the Chesapeake Bay. Located within the Bay is Naval Station Norfolk, the world’s largest naval military installation, and the Port of Virginia, the sixth busiest container port in the United States. These large seaports, combined with the presence of recreational boaters, commercial fishing vessels, and sport-fishing boats, result in a constant heavy flow of vessel traffic through the mouth of the Chesapeake Bay and adjacent areas. From December 2015 to February 2017, 35 satellite tags were deployed on humpback whales to gain a better understanding on the occurrence, movements, site-fidelity, and overall behavior of this species within this high-traffic region. The tags transmitted data for an average of 13.7 days (range 2.7–43.8 days). Location data showed that at some point during tag deployment, nearly all whales occurred within, or in close proximity to, the shipping channels located in the study area. Approximately one quarter of all filtered and modeled locations occurred within the shipping channels. Hierarchical state-space modeling results suggest that humpback whales spend considerable time (82.0%) engaged in foraging behavior at or near the mouth of the Chesapeake Bay. Of the 106 humpback whales photo-identified during this research, nine individuals (8.5%) had evidence of propeller strikes. One whale that had previously been tagged and tracked within shipping channels, was found dead on a local beach; a fatality resulting from a vessel strike. The findings from this study demonstrate that a substantial number of humpback whales frequent high-traffic areas near the mouth of the Chesapeake Bay, increasing the likelihood of injurious vessel interactions that can result in mortalities.